Reinforced Concrete Buildings Following NSR-10 vs Quetame Earthquake Registered on Bogotá D.C. (2012)
A three dimensional nonlinear dynamic analysis of 6 concrete reinforced buildings of 5, 12 and 20 stories, designed according to NSR-10 and seismic response zoning for Bogotá 2010 version is presented. These 6 buildings were subjected to 78 seismic signals of the Quetame earthquake (2008) registered in 26 stations of the Bogotá’s accelerometer array (RAB). “Piedmont-B” and“Lacustrine-500” absolute acceleration design response spectra from the seismic response zoning of Bogota (2010) were used to design buildings analyzed. Plastic hinges were deﬁned and assigned to each of the structural elements of the 6 buildings, and for columns the interaction diagrams were established too. With these nonlinear parameters, the 6 structures were subject simultaneously to the time history registers North-South, East-West and vertical.For each building and for each seismic register the performance levels, the interstory drifts, roof displacements and base shear demanded were determined. With this information seismic demand maps were plotted for Bogota for each one of buildings. The results suggest that, buildings designed under the new rules to Bogotá and provisions of NSR-10, develop strong damage level, related to limit states, such as: “llife security” for low-magnitude quake, was the Quetame earthquake, so far, from the design scenario.